Influence of Implant-Retained Silicone Oculo-palpebral Prosthesis on Stress Distribution: A Pilot Study Using A Photoelastic Model - Cortizo, Daniela Lattuf [UNESP]; Kodama, Ricardo Matsura [UNESP]; Piras de Oliveira, Joaquim Augusto; Melo Mesquita, Alfredo Mikail [UNESP]; Lagana, Dalva Cruz; Dib, Luciano Lauria [UNESP] (Quintessence Publishing Co Inc, 2015)
Purpose: The purpose of this pilot study was to evaluate the behavior of stresses surrounding orbital model implants subjected to a load of a silicone oculo-palpebral prosthesis. Materials and Methods: A photoelastic model was constructed mimicking the orbital cavity of an adult patient who underwent left orbital resection. Two 3.75 x 5-mm extraoral implants with 3.75 x 5.25-mm magnetic connectors were placed in the model to anchor a silicone oculo-palpebral prosthesis. The stress generated by prosthesis retention was evaluated using photoelasticity at 15, 30, and 60 minutes. The polariscope images were analyzed qualitatively at five areas surrounding the implants. These same areas were analyzed quantitatively using Matlab software based on the RGB color pattern. Data were compared with the Wilcoxon test. Results: Using fringe localization, the qualitative analysis demonstrated that the area between the implants had the greatest stress. The quantitative analysis showed that the peri-implant stress increased significantly in proportion to the increase in prosthesis retention time. Conclusion: The oculo-palpebral prosthesis generated stress around the implants, and the stress intensity was directly proportional to the duration of use.
Keywords: extraoral implant; oculo-palpebral prosthesis; photoelasticity; stress analysis